Lithium-ion battery and application for the same

The lithium ion battery design addresses conductivity and cycle life issues by using ethylene carbonate and additives to form dense films on electrodes, improving the stability and performance of lithium manganese iron phosphate batteries.

JP2025013110AActive Publication Date: 2025-01-24ENVISION DYNAMICS TECH (JIANGSU) CO LTD +4
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023203487
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-13
Filing Date
2023-11-30
Publication Date
2025-01-24
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate batteries suffer from low electrical conductivity, poor cycle performance, and damage to the solid electrolyte interface (SEI) due to manganese ion dissolution, leading to reduced battery life and performance.

Method used

A lithium ion battery design incorporating a positive electrode with lithium manganese iron phosphate, a non-aqueous solvent containing ethylene carbonate, and additives like 1,3-propane sultone for a dense CEI film, and a negative electrode with vinylene carbonate for a dense SEI film, along with controlled solvent ratios and lithium salts, to enhance conductivity and stability.

Benefits of technology

The design improves electrolyte conductivity, reduces oxidative decomposition, and continuously repairs the SEI film, enhancing cycle life and high-temperature performance of lithium manganese iron phosphate batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013110000001_ABST
    Figure 2025013110000001_ABST
Patent Text Reader

Abstract

To provide a lithium-ion battery that can improve electrolyte stability, improve the cycle performance of the lithium-ion battery, and improve the performance of the lithium-ion battery at high temperatures.SOLUTION: The lithium-ion battery has a double-sided surface density of 35 mg / cm2 or more. The lithium-ion battery includes a positive electrode sheet 10 containing a positive electrode active material containing lithium iron manganese phosphate, a negative electrode sheet 20, a separator 30 disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte 40 filled between the positive electrode sheet, the negative electrode sheet, and the separator. The electrolyte includes a non-aqueous solvent. The non-aqueous solvent includes ethylene carbonate. The mass ratio of ethylene carbonate in the non-aqueous solvent is 10 wt.% to 35 wt.%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of lithium ion batteries, in particular to lithium ion batteries and their applications. [Background technology]

[0002] At present, the market size of lithium-ion batteries has expanded significantly due to the rapid development of lithium-ion batteries in the fields of electric vehicles and large-scale energy storage. In particular, lithium iron phosphate batteries have become the mainstream in the development of lithium-ion batteries due to their low cost and long cycle life. However, the specific capacity of current lithium iron phosphate materials is close to the theoretical value, so the energy density of lithium iron phosphate batteries is approaching its limit.

[0003] Lithium manganese iron phosphate is obtained by replacing part of the iron in lithium iron phosphate with manganese, which can increase the energy density of lithium manganese iron phosphate without increasing the cost of the positive electrode active material. However, the electrical conductivity of lithium manganese iron phosphate is low. In lithium-ion batteries, the dynamic performance of the battery is low, leading to a decrease in cycle performance. During the cycle of lithium manganese iron phosphate batteries, the dissolution of manganese ions destroys the solid electrolyte interphase (SEI), causing an increase in the consumption of active lithium in the battery and an increase in the resistance of the negative electrode SEI film, which affects the cycle life of the battery. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a lithium ion battery and its application, which can improve the stability of the electrolyte, improve the cycle performance of the lithium ion battery, and improve the performance of the lithium ion battery at high temperatures. [Means for solving the problem]

[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery comprising at least the following components:

[0006] Double-sided surface density is 35mg / cm 2 A positive electrode sheet comprising the above and a positive electrode active material containing lithium iron manganese phosphate;

[0007] A negative electrode sheet;

[0008] A separator disposed between the positive electrode sheet and the negative electrode sheet;

[0009] An electrolyte filled between a positive electrode sheet, a negative electrode sheet, and a separator, the electrolyte including a non-aqueous solvent, the non-aqueous solvent including ethylene carbonate, and a mass ratio of the ethylene carbonate in the non-aqueous solvent being 10% by weight to 35% by weight.

[0010] In one embodiment of the present invention, the molecular formula of the lithium manganese iron phosphate is Li x Mn y Fe 1-y PO4, where 0.95≦x≦1.05 and 0.4≦y≦0.7.

[0011] In one embodiment of the present invention, the mass proportion of ethylene carbonate in the non-aqueous solvent is 15% by weight to 30% by weight.

[0012] In one embodiment of the present invention, the electrolyte further includes a positive electrode film-forming additive, the positive electrode film-forming additive includes 1,3-propane sultone, and the content of the positive electrode film-forming additive in the electrolyte is 0.01% by weight to 5% by weight.

[0013] In one embodiment of the present invention, the electrolytic solution further includes an anode film-forming additive, the anode film-forming additive includes vinylene carbonate, and the content of the anode film-forming additive in the electrolytic solution is 0.1% by weight to 10% by weight.

[0014] In one embodiment of the present invention, the non-aqueous solvent further comprises any one or a combination of at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, or diethyl carbonate.

[0015] In one embodiment of the present invention, the non-aqueous solvent further comprises ethyl methyl carbonate and dimethyl carbonate, and the mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate is (0.5-4.5):(2.75-4.75):(2.75-4.75).

[0016] In one embodiment of the present invention, the content of the non-aqueous solvent in the electrolytic solution is 60% by weight to 85% by weight.

[0017] In one embodiment of the present invention, the electrolyte further comprises a lithium salt, and the lithium salt comprises any one or a combination of at least two of LiPF6, LiBF4, LiFSI, LiTFSI, LiBOB, LiODFP, LiODFB, LiPO2F2, or CF3SO3Li.

[0018] In one embodiment of the present invention, the concentration of the lithium salt in the electrolyte is 0.1 mol / L to 2 mol / L.

[0019] The present invention further provides an electrochemical device comprising the lithium ion battery described above. Effect of the Invention

[0020] In summary, the present invention provides a lithium-ion battery and its application, which can improve the conductivity of the electrolyte, ensure the oxidation stability of the electrolyte, enhance the kinetics of the lithium-ion battery, and improve the cycle performance. A dense CEI film can be generated on the surface of the positive electrode to reduce the oxidative decomposition of the electrolyte. A dense SEI film can be generated on the negative electrode. The SEI film is continuously repaired during cycling, so that the damage to the SEI film of the negative electrode caused by the dissolution of manganese ions can be reduced, and the cycle life of the lithium manganese iron phosphate battery can be effectively improved. By controlling the type and content of the solvent, the positive electrode additive, and the negative electrode additive, the stability of the electrolyte can be improved, the cycle performance of the lithium-ion battery can be improved, and the performance of the lithium-ion battery at high temperatures can be improved. [Brief description of the drawings]

[0021] In order to more clearly describe the embodiments of the present disclosure or the technical solutions of the prior art, the drawings necessary for describing the embodiments or related art are briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present disclosure. Those skilled in the art can obtain other drawings based on these drawings without creative efforts. [Figure 1] 1 is a schematic diagram of a lithium ion battery according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the present invention will be described with reference to specific examples. Those skilled in the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification. The present disclosure can also be implemented or applied through other different specific implementations. Various details of the present specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present disclosure.

[0023] It is understood that the present disclosure may be embodied in different forms and should not be construed as limited to the embodiments set forth herein, but rather these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the disclosure to those skilled in the art.

[0024] The technical solutions of the present disclosure are described in further detail below with reference to some embodiments and drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present disclosure. Based on the embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work fall within the scope of protection of the present disclosure.

[0025] Please refer to FIG. 1. The present invention provides a lithium ion battery including a positive electrode sheet 10, a negative electrode sheet 20, a separator 30, and an electrolyte 40. The separator 30 is located between the positive electrode sheet 10 and the negative electrode sheet 20. The electrolyte 40 is filled between the positive electrode sheet 10, the negative electrode sheet 20, and the separator 30. The present invention does not limit the type and shape of the lithium ion battery. In one embodiment of the present invention, the lithium ion battery is a primary battery or a secondary battery. The secondary battery is, for example, a pouch-type battery, a square battery, or a cylindrical battery. In this embodiment, a pouch-type secondary battery will be described as an example.

[0026] Please refer to FIG. 1. In one embodiment of the present invention, the positive electrode sheet 10 includes a positive electrode collector and a positive electrode active material layer applied to one side of the positive electrode collector. The positive electrode active material layer includes a positive electrode active material, a binder, a conductive agent, and the like. The positive electrode collector includes, for example, a foil body made of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, or the like that has been subjected to a surface treatment. As the form of the positive electrode collector, in addition to a foil body, any one or a combination of a plurality of films, meshes, pores, foams, nonwoven fabrics, and the like can be adopted. The thickness of the positive electrode collector is, for example, 8 μm to 15 μm. In this embodiment, the positive electrode collector is, for example, an aluminum foil.

[0027] In one embodiment of the present invention, the positive electrode active material is selected from, for example, lithium manganese iron phosphate, the molecular formula of which is Li x Mn y Fe 1-y PO4, where 0.95≦x≦1.05 and 0.4≦y≦0.7. The binder is, for example, selected from one or more of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene, or polymerized styrene butadiene rubber (SBR). The conductive agent is, for example, selected from one or more of conductive carbon black (SuperP, SP), acetylene black, carbon nanotubes, graphene, etc.

[0028] See FIG. 1. In one embodiment of the present invention, the positive electrode active material is, for example, LiMn 0.6 Fe 0.4 The positive electrode active material is PO4, the binder is selected from polyvinylidene fluoride, and the conductive agent is selected from acetylene black. After mixing the positive electrode active material, acetylene black, and polyvinylidene fluoride in a weight ratio of, for example, 95:3:2, an organic solvent is added and stirred until the system becomes uniform to obtain a positive electrode slurry. The organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The positive electrode slurry is uniformly applied onto an aluminum foil and dried, and then the dried aluminum foil is processed by cold pressing or the like to obtain a positive electrode sheet 10. In this embodiment, the surface density on both sides of the positive electrode sheet is 35 mg / cm 2 That's all.

[0029] Please refer to FIG. 1. In one embodiment of the present invention, the negative electrode sheet 20 includes, for example, a negative electrode current collector and a negative electrode active material layer applied to at least one surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a binder, a conductive agent, a thickener, and the like. The negative electrode current collector is, for example, any one selected from a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foamed copper current collector, a stainless steel current collector, and the like. The thickness of the negative electrode current collector is, for example, 8 μm to 15 μm.

[0030] Please refer to FIG. 1. In one embodiment of the present invention, the negative electrode active material is selected from any one or a combination of at least two of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide compound, silicon carbide compound, or lithium titanate. The binder is, for example, selected from any one or more of polyvinylidene fluoride, polyamide, polypropylene, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, or styrene butadiene rubber. The conductive agent is, for example, selected from any one or more of conductive carbon black, acetylene black, carbon nanotubes, graphite, etc. In one embodiment of the present invention, the negative electrode current collector is, for example, selected from copper foil. The negative electrode active material is, for example, selected from graphite. The conductive agent is, for example, selected from acetylene black. The binder is, for example, selected from styrene butadiene rubber. The thickener is, for example, selected from sodium carboxymethyl cellulose. In one embodiment of the present invention, graphite, acetylene black, styrene butadiene rubber, and sodium carboxymethylcellulose were mixed in a mass ratio of, for example, 96:2:1:1, and deionized water was added and thoroughly stirred to obtain a negative electrode slurry. The negative electrode slurry was uniformly applied onto a copper foil, and then subjected to processes such as drying and cold pressing to obtain a negative electrode sheet 20.

[0031] Please refer to Fig. 1. In one embodiment of the present invention, the separator 30 is, for example, a polyethylene (PE) film, a polypropylene (PP) film, a glass fiber film, a polyethylene film, or a composite film, and the thickness of the separator is, for example, 9 μm to 15 μm. In this embodiment, a polyethylene film with a thickness of 8 μm to 10 μm is selected as the base film of the separator, and a nano-alumina coating with a thickness of 2 μm to 4 μm is coated on the base film to obtain the separator 30.

[0032] Please refer to Fig. 1. In one embodiment of the present invention, the electrolyte 40 includes at least a non-aqueous solvent, a lithium salt, and an additive. 2 In the above cases, in order to improve the conductivity of the electrolyte, the non-aqueous solvent contains ethylene carbonate (EC) with a high dielectric constant, and the mass ratio of ethylene carbonate in the non-aqueous solvent is 10% by weight to 35% by weight, or 15% by weight to 30% by weight. If the content of EC is too low, the high conductivity of the electrolyte 40 cannot be guaranteed, and the dynamic performance of the high-density lithium manganese iron phosphate battery cannot be improved. If the content of EC is too high, the oxidation stability of the electrolyte 40 decreases, and an irreversible oxidative decomposition reaction occurs in the positive electrode, resulting in a decrease in the cycle characteristics of the battery. Therefore, the conductivity of the electrolyte can be improved by adding and controlling the content of ethylene carbonate in the electrolyte. At the same time, the amount of ethylene carbonate added can also be controlled to prevent a decrease in the oxidation stability of the electrolyte.

[0033] Please refer to Fig. 1. In one embodiment of the present invention, the non-aqueous solvent further includes, for example, any one or a combination of at least two of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), or diethyl carbonate (DEC). The non-aqueous solvent includes, for example, ethyl methyl carbonate and dimethyl carbonate, and the mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate is (0.5 to 4.5):(2.75 to 4.75):(2.75 to 4.75). In one embodiment of the present invention, the mass content of the non-aqueous solvent in the electrolytic solution 40 is, for example, 60% to 85%. When preparing the electrolyte, when the nitrogen content in the glove box is 99.999%, the actual oxygen content in the glove box is less than 0.1 ppm, and the water content is less than 0.1 ppm, battery grade ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate are mixed uniformly, and then the fully dried lithium salt is added to the above-mentioned non-aqueous solvent, and additives are added to prepare the non-aqueous electrolyte for lithium ion batteries.

[0034] Please refer to FIG. 1. In one embodiment of the present invention, the additive further includes a positive electrode film forming additive and a negative electrode film forming additive. The positive electrode film forming additive includes 1,3-propanesultone (PS), and the content of the positive electrode film forming additive in the electrolyte 40 is, for example, 0.01% by weight to 5% by weight, for example, 0.1% by weight to 2% by weight. The positive electrode film forming additive forms a dense cathode-electrolyte interphase (CEI) on the surface of the positive electrode, thereby reducing the oxidative decomposition of the electrolyte 40. If the mass content of the positive electrode film forming additive is too low, a dense CEI film cannot be formed on the positive electrode to prevent the oxidative decomposition of the electrolyte 40. If the content of the positive electrode film forming additive is too high, an excessively thick CEI film is formed, the interface resistance of the positive electrode increases, and the dynamic performance and cycle life of the battery are reduced. Therefore, the mass content of the positive electrode film-forming additive is controlled to ensure the stability of the positive electrode, reduce the decomposition of the electrolyte, and improve the cycle characteristics of the lithium-ion battery.

[0035] Please refer to FIG. 1. In one embodiment of the present invention, the negative electrode film-forming additive includes vinylene carbonate (VC), and the content of the negative electrode film-forming additive in the electrolyte 40 is 0.1% by weight to 10% by weight, for example, 0.5% by weight to 3% by weight, to form a high-quality SEI film on the negative electrode. If the mass content of VC is too low, a dense SEI film cannot be formed, and the SEI film cannot be repaired continuously in a timely manner during cycling. Under such circumstances, manganese ions dissolved from the positive electrode will rapidly deteriorate the negative electrode interface, causing lithium loss and destruction of the dynamic performance of the negative electrode, and the cycle life of the battery will rapidly decrease. If the mass percentage of VC is too high, the viscosity of the electrolyte will increase rapidly, the conductivity of the electrolyte 40 will decrease, and the dynamic performance of the lithium-ion battery will decrease. Therefore, by controlling the content of VC, VC can form a dense SEI film on the negative electrode, and the SEI film can be continuously repaired during cycling, thus reducing the damage to the SEI film of the negative electrode caused by the dissolution of manganese ions. The combined use of EC, PS and VC can improve the dynamic performance of lithium-ion batteries and effectively extend the cycle life of lithium manganese iron phosphate batteries.

[0036] Please refer to FIG. 1. In one embodiment of the present invention, the electrolyte 40 further includes a lithium salt. The lithium salt is selected from, for example, any one or a combination of at least two of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bisfluorosulfonimide (LiFSI), lithium bistrifluoromethanesulfonimide (LiTFSI), lithium bisoxaborate (LiBOB), lithium difluorobisoxalophosphate (LiODFP), lithium difluorooxaloborate (LiODFB), lithium difluorophosphate (LiPO2F2), or lithium triflate (LiCF3SO3). In one embodiment of the present invention, the concentration of the lithium salt in the electrolyte 40 is 0.1 mol / L to 2 mol / L.

[0037] Please refer to Fig. 1. In one embodiment of the present invention, the above-mentioned positive electrode sheet 10, separator 30, and negative electrode sheet 20 are stacked in order with the separator 30 positioned between the positive electrode sheet 10 and the negative electrode sheet 20 to separate them, and then stacked to obtain a bare battery cell. The bare battery cell is placed in an aluminum plastic film, baked at 80°C to remove moisture, and then the electrolyte 40 is injected and sealed. The sealed bare battery cell is then left to stand, hot and cold pressed, molded, clamped, and capacity divided to obtain a completed soft-pack type lithium ion battery.

[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. Appropriate modifications are possible within the scope of the present invention, and all such modifications are within the technical scope of the present invention.

[0039] Example 1

[0040] Preparation of positive electrode sheet: LiMn as positive electrode active material 0.6 Fe 0.4 PO4, acetylene black as a conductive agent, and polyvinylidene fluoride as a binder were selected and mixed in a mass ratio of 95:3:2. After the positive electrode active material, binder, and conductive agent were uniformly mixed, a solvent selected from N-methylpyrrolidone was added and stirred until the mixture became uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry was uniformly applied onto an aluminum foil, dried, and then cold pressed to obtain a positive electrode sheet. The surface density on both sides of the positive electrode sheet was 38 mg / cm. 2 It was.

[0041] Preparation of negative electrode sheet: Graphite was selected as the negative electrode active material, acetylene black as the conductive agent, styrene butadiene rubber as the binder, and sodium carboxymethylcellulose as the thickener, and mixed in a mass ratio of 96:2:1, deionized water was added, and the mixture was thoroughly stirred to obtain a negative electrode slurry. The negative electrode slurry was uniformly applied onto copper foil, dried, and then cold pressed to obtain a negative electrode sheet.

[0042] Preparation of electrolyte: The nitrogen content in the glove box was 99.999%, the actual oxygen content in the glove box was 0.1 ppm, and the water content was 0.1 ppm. The non-aqueous solvent was composed of ethylene carbonate, ethyl methyl carbonate, and carbonic acid in a mass ratio of 2:4:4. The total mass of the electrolyte was taken as 100%, and lithium salt and additives were added so that the concentration of lithium hexafluorophosphate was 1 mol / L, the mass percentage of PS content was 1 wt%, and the mass percentage of VC was 2 wt%, to obtain an electrolyte.

[0043] Selection of separator: 9 μm polyethylene was selected as the base film, and a 3 μm-thick nano-alumina coating was coated on the base film to obtain the separator.

[0044] Battery fabrication: A positive electrode sheet, a separator, and a negative electrode sheet were laminated in this order so that the separator was interposed between the positive electrode sheet and the negative electrode sheet, and these were laminated to obtain a bare battery cell. The bare battery cell was wrapped in an aluminum plastic film, baked at 80°C to remove moisture, and then injected with electrolyte 40 and sealed. The sealed bare battery cell was then left to stand, hot and cold pressed, molded, clamped, and volume-divided to obtain a lithium-ion battery.

[0045] Example 2

[0046] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 0.5:4.75:4.75, and the other steps were the same as in Example 1.

[0047] Example 3

[0048] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 1:4.5:4.5, and the other steps were the same as in Example 1.

[0049] Example 4

[0050] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 1.5:4.25:4.25, and the other steps were the same as in Example 1.

[0051] Example 5

[0052] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 3:3.5:3.5, and the other steps were the same as in Example 1.

[0053] Example 6

[0054] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 3.5:3.25:3.25, and the other steps were the same as in Example 1.

[0055] Example 7

[0056] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 4.5:2.75:2.75, and the other steps were the same as in Example 1.

[0057] Example 8

[0058] The mass percentage of PS in the electrolyte was 0.005% by weight, and the other steps were the same as in Example 1.

[0059] Example 9

[0060] The mass percentage of PS in the electrolyte was 0.01% by weight, and the other steps were the same as in Example 1.

[0061] Example 10

[0062] The mass percentage of PS in the electrolyte was 0.1 wt %, and the other steps were the same as in Example 1.

[0063] Example 11

[0064] The mass percentage of PS in the electrolyte was 3 wt %, the concentration of LiFSI was 0.6 mol / L, and the other steps were the same as in Example 1.

[0065] Example 12

[0066] The mass percentage of PS in the electrolyte was 5 wt %, and the other steps were the same as in Example 1.

[0067] Example 13

[0068] The mass percentage of PS in the electrolyte was 8 wt %, and the other steps were the same as in Example 1.

[0069] Example 14

[0070] The mass percentage of VC in the electrolyte was 0.05% by weight, and the other steps were the same as in Example 1.

[0071] Example 15

[0072] The mass percentage of VC in the electrolyte was 0.1 wt %, and the other steps were the same as in Example 1.

[0073] Example 16

[0074] The mass percentage of VC in the electrolyte was 0.5 wt %, and the other steps were the same as in Example 1.

[0075] Example 17

[0076] The mass percentage of VC in the electrolyte was 3 wt %, and the other steps were the same as in Example 1.

[0077] Example 18

[0078] The mass percentage of VC in the electrolyte was 10 wt %, and the other steps were the same as in Example 1.

[0079] Example 19

[0080] The mass percentage of VC in the electrolyte was 15 wt %, and the other steps were the same as in Example 1.

[0081] Comparative Example 1

[0082] The mass ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in the electrolytic solution was 0:5:5, and the other operations were the same as in Example 1.

[0083] Comparative Example 2

[0084] The other operations were the same as in Example 1, except that no PS was added to the electrolyte.

[0085] Comparative Example 3

[0086] The other operations were the same as in Example 1, except that VC was not added to the electrolyte.

[0087] In the present invention, performance tests such as tests of capacity retention rate in normal temperature cycles and high temperature cycles of lithium ion batteries were carried out on the lithium ion batteries obtained in Examples 1 to 19 and Comparative Examples 1 to 3. The results are shown in Table 1.

[0088] In one embodiment of the present invention, the capacity retention test in normal temperature cycles was performed as follows. The lithium ion battery was charged to 4.2V at a constant current of 1C at a temperature of 25°C, and then charged at a constant voltage of 4.2V until the current was less than 0.05C. After leaving it for 10 minutes, the lithium ion battery was discharged to 2.5V at a constant current of 1C. The discharge capacity of the lithium ion battery in this state was tested, and the result was the discharge capacity of the first cycle. The above process was performed on the battery for multiple cycles, and the capacity retention rate of the battery after 400 cycles was calculated. The relative capacity retention rate after cycling was calculated according to the following formula: Capacity retention rate (%) = (discharge capacity equivalent to 400 cycles / discharge capacity at 1st cycle) x 100%

[0089] In one embodiment of the present invention, the capacity retention rate test in high temperature cycles was performed as follows. The lithium manganese iron phosphate battery was charged to 4.2V at a constant current of 1C at a temperature of 45°C, and then charged at a constant voltage of 4.2V until the current was less than 0.05C. After leaving it for 10 minutes, the lithium manganese iron phosphate battery was discharged to 2.5V at a constant current of 1C, and the discharge capacity of the lithium manganese iron phosphate battery in this state was tested, and the result was the discharge capacity of the first cycle. The above process was performed on the battery for multiple cycles, and the capacity retention rate of the battery after 400 cycles was calculated. The relative capacity retention rate after cycling was calculated according to the following formula: Capacity retention rate (%) = (discharge capacity equivalent to 400 cycles / discharge capacity at 1st cycle) x 100% The performance test results of the lithium ion batteries of Examples 1 to 19 and Comparative Examples 1 to 3 are shown below.

[0090] [Table 1]

[0091] Please refer to Table 1. Referring to Examples 1 to 19 and Comparative Example 1, it can be seen that by adding ethylene carbonate to the electrolyte and controlling the amount of ethylene carbonate, the retention rate of the lithium ion battery after normal temperature cycle and the retention rate of the lithium ion battery after high temperature cycle are improved at the same time. That is, by adding ethylene carbonate, the conductivity of the electrolyte is increased, and the cycle performance of the high density lithium ion battery is improved, and by controlling the content of ethylene carbonate, it is possible to prevent the stability of the electrolyte from being reduced due to an excessive content. Comparing Examples 1 to 19 and Comparative Example 2, it can be seen that by adding the positive electrode additive PS, a dense CEI film is formed on the positive electrode, and the power performance and cycle performance of the lithium ion battery are improved. Comparing Examples 1 to 19 and Comparative Example 3, it can be seen that by adding the negative electrode additive VC, a dense SEI film is formed on the negative electrode, the SEI film is continuously repaired during the cycle, and damage to the negative electrode SEI film caused by the dissolution of manganese ions can be reduced. In this way, the cycle life of the lithium manganese iron phosphate battery can be effectively improved.

[0092] Please refer to Table 1. From Comparative Examples 1 to 7, it can be seen that as the content of ethylene carbonate increases, the capacity retention rate at room temperature and high temperature first increases and then decreases. When the ethylene carbonate is 30% by weight of the non-aqueous solvent, the capacity retention rate is the highest, and as the content of dimethyl carbonate increases, the dynamic performance of the lithium ion battery improves. However, if the content of dimethyl carbonate is too high, the oxidation stability of the electrolyte is deteriorated, causing a rapid capacity decrease. Therefore, in order to ensure the performance of the lithium ion battery, it is necessary to control the amount of ethylene carbonate.

[0093] Please refer to Table 1. Comparing Example 1 with Examples 8 to 13, it can be seen that as the content of the positive electrode additive PS increases, the capacity retention rate after cycling first increases and then decreases, and the capacity retention rate after normal temperature cycling and the capacity retention rate after high temperature cycling change synchronously. When the content of PS is 3 wt%, the overall performance of the lithium ion battery is optimal, which indicates that as the content of PS increases, a dense CEI film can be formed on the positive electrode, which can prevent the oxidative decomposition of the electrolyte. However, if the content of PS is too high, the CEI film becomes too thick, which increases the interface resistance of the positive electrode, and reduces the dynamic performance and cycle life of the lithium ion battery.

[0094] Please refer to Table 1. Comparing Example 1 with Examples 14 to 19, it can be seen that as the content of the negative electrode additive VC increases, the capacity retention rate after cycling first increases and then decreases. When the content of VC is between 0.5% by weight and 3% by weight, the overall performance of the lithium-ion battery reaches an optimal level, which indicates that as the content of VC increases, a dense SEI film is formed on the negative electrode, and the SEI film is continuously repaired during cycling, thereby reducing the damage to the SEI film of the negative electrode caused by the dissolution of manganese ions, and effectively improving the cycle life of the lithium manganese iron phosphate battery. At the same time, problems such as SEI damage and excessive impedance caused by the VC content being too high or too low can be prevented. That is, by adding ethylene carbonate, PS, and VC to the electrolyte and controlling their contents, the performance of the lithium manganese iron phosphate battery can be improved and the cycle characteristics of the battery can be improved. [Industrial Applicability]

[0095] In summary, the present invention provides a lithium ion battery and its application. By selecting the components of the non-aqueous solvent, the conductivity of the electrolyte can be improved, the oxidation stability of the electrolyte can be ensured, the dynamic performance of the lithium ion battery can be improved, and the cycle characteristics can be improved. By controlling the positive electrode additive and its content, a dense CEI film can be formed on the surface of the positive electrode to reduce the oxidative decomposition of the electrolyte. By controlling the negative electrode additive and its content, a dense SEI film can be formed on the negative electrode, and the SEI film can be continuously repaired during cycling, thereby reducing the damage to the negative electrode SEI film caused by the dissolution of manganese, and effectively improving the cycle life of the lithium manganese iron phosphate battery. By controlling the type and content of the solvent, positive electrode additive, and negative electrode additive, the stability of the electrolyte can be improved, the cycle performance of the lithium ion battery can be improved, and the performance of the lithium ion battery at high temperatures can be improved.

[0096] The above description is only a preferred embodiment of the present disclosure and only a description of the technical principles used. Those skilled in the art should understand that the scope of disclosure contained in this disclosure is not limited to the technical solution formed by a specific combination of the above technical features, and should also include other technical solutions formed by any combination of the above technical features or their equivalent features, such as (but not limited to) the technical solutions formed by replacing the above features with technical features having similar functions disclosed in this application, without departing from the concept of the present invention.

[0097] Except for the technical features described in this specification, the remaining technical features are known to those skilled in the art, and in order to highlight the innovative features of the present disclosure, the remaining technical features will not be described in detail herein. [Explanation of symbols]

[0098] 10: Positive electrode sheet 20: Negative electrode sheet 30: Separator 40: Electrolyte

Claims

1. Both sides have a surface density of 35 mg / cm 2 A positive electrode sheet comprising the above and a positive electrode active material containing lithium iron manganese phosphate; A negative electrode sheet; a separator disposed between the positive electrode sheet and the negative electrode sheet; an electrolytic solution filled between the positive electrode sheet, the negative electrode sheet, and the separator, the electrolytic solution including a non-aqueous solvent, the non-aqueous solvent including ethylene carbonate, and a mass ratio of the ethylene carbonate in the non-aqueous solvent being 10% by weight to 35% by weight; At least one lithium ion battery.

2. The molecular formula of the lithium manganese iron phosphate is Li x Mn y Fe 1-y P.O. 4 2. The lithium ion battery of claim 1 , wherein 0.95≦x≦1.05 and 0.4≦y≦0.

7.

3. 2. The lithium ion battery according to claim 1, wherein the mass ratio of the ethylene carbonate in the non-aqueous solvent is 15% by weight to 30% by weight.

4. The lithium ion battery according to claim 1, wherein the electrolyte further comprises a positive electrode film forming additive, the positive electrode film forming additive comprises 1,3-propane sultone, and the content of the positive electrode film forming additive in the electrolyte is 0.01% by weight to 5% by weight.

5. The lithium ion battery according to claim 1, wherein the electrolyte further comprises an anode film forming additive, the anode film forming additive comprises vinylene carbonate, and the content of the anode film forming additive in the electrolyte is 0.1% by weight to 10% by weight.

6. 2. The lithium ion battery according to claim 1, wherein the non-aqueous solvent further comprises any one or a combination of at least two of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, or diethyl carbonate.

7. 2. The lithium ion battery according to claim 1, wherein the non-aqueous solvent further contains ethyl methyl carbonate and dimethyl carbonate, and the mass ratio of the ethylene carbonate, the ethyl methyl carbonate, and the dimethyl carbonate is (0.5-4.5):(2.75-4.75):(2.75-4.75).

8. 2. The lithium ion battery according to claim 1, wherein the content of the non-aqueous solvent in the electrolyte is 60% by weight to 85% by weight.

9. The electrolyte further includes a lithium salt, and the lithium salt is LiPF 6 , LiBF 4 , LiFSI, LiTFSI, LiBOB, LiODFP, LiODFB, LiPO 2 F 2 Or CF 3 SO 3 2. The lithium ion battery of claim 1 , comprising any one or a combination of at least two of Li.

10. 10. The lithium ion battery according to claim 9, wherein the concentration of the lithium salt in the electrolyte is 0.1 mol / L to 2 mol / L.

11. 13. An electrochemical device comprising the lithium ion battery of claim 1.

Citation Information

Patent Citations

  • Lithium ion battery

    CN115882043A

  • Lithium ion battery

    CN116404253A

  • Secondary battery using non-aqueous electrolyte

    JP2004063145A

  • Secondary battery

    JP2006156315A

  • Electrolyte and battery

    JP2007005293A